Increasing Students Creativity Learning In Mathematic Subject Through Realistic Mathematic Education Approach in Fifth Grade SDN Gulon - Agustina, Sulistyani (Universitas Sebelas Maret, 2022)
This study aims to increase the creativity and learning outcomes of fifth grade students at SD Negeri Gulon through a Realistic Mathematical Education approach. This type of research is Classroom Action Research. Data collection techniques through pre-test and post-test. The results showed that the indicators of frequently asking questions with weight increased from 28.57% in the first cycle to 82.86% in the second cycle. Indicators providing ideas and suggestions for a problem increased from 31.43% to 80%. The indicator can work alone from 62.85% to 85.71%. Indicators of having their own opinion are not easily influenced by others increasing from 40% to 77.14%. While the indicator of being able to develop an idea increased from 34.29% to 82.86%. In addition to the increase in interest indicators, student learning outcomes also increased, namely the pre-cycle only reached 46.71%, the first cycle reached 57.14%, the second cycle reached 94.29%.